Gene-Associated snp discovery and molecular cloning of full-length cDNA of cinnamate 4-hydroxylase and cinnamy alcohol dehydrogenase in a tropical timber tree Neolamarckia cadamba TREE Neolamarckia cadamba - Tchin, Boon Ling (University Malaysia Sarawak, UNIMAS, 2013)
Neolamarckia cadamba, or locally known as Kelampayan is one of the indigenous tree species that are selected for forest plantation establishment in Sarawak due to the high productivity and short rotation time of this species. Understanding the structure and composition of Kelampayan wood through genome integration is vital to better utilize this wood material. Concurrently, the Kelampayan wood formation genomic resource database, aka Cadamomics (10,368 ESTs) has been developed, and this opens the gateway for researchers to deeply explore the genomic basic of Kelampayan. EST database is a useful resource for gene discovery. Further analysis on this database generated two full-length lignin biosynthesis genes, namely C4H and CAD. Validation by RT-PCR and full-length gene specific primers had confirmed the identities of the genes discovered. The full-length C4H cDNA, designated as NcC4H is 1,651 bp long, with a 1,518 bp open reading frame encoding a protein of 505 amino acids, a 18 bp 5’-UTR and a 115 bp 3’-UTR. The NcC4H showed higher identity with the class I C4Hs, which is preferentially involved in the phenylpropanoid biosynthesis pathway. Meanwhile, sequence analysis of the full-length CAD cDNA, designated as NcCAD, showed that it is 1,240 bp long with a 1,086 bp open reading frame encoding a protein of 361 amino acids, a 68 bp 5’-UTR and a 86 bp 3’-UTR. Phylogenetic analysis revealed that NcCAD was grouped in the cluster containing both CAD and SAD genes, in which both genes were involved in lignin biosynthesis. The full-length NcC4H and NcCAD cDNA identified serve as good candidate genes for association genetics studies in Kelampayan. Association genetics study is a powerful approach to detect potential genetic variants, i.e. SNPs, underlying the common and complex adaptive traits. Thus far, single nucleotide polymorphisms (SNPs) detected in C4H and CAD genes were known to be correlated with some other phenotypic variations in forest tree species rather than with lignin production only. Hence, attempts were made to discover SNPs from the partial C4H and CAD genomic DNA sequences. Overlapping primers were designed to flank the partial C4H and CAD DNA from 12 Kelampayan samples. The amplified DNA fragments were cloned and sent for sequencing. Furthermore, wood cores were collected and the basic wood density was measured for each tree. Sequence variation analysis revealed that there were 60 and 32 SNPs detected in the partial C4H and CAD DNA sequences, respectively. The SNPs detected were distributed throughout the exon, intron, 5’-UTR and 3’-UTR regions. Among the SNPs detected in the exon regions of C4H, 16 were synonymous mutations and eight were nonsynonymous mutations. For CAD, six SNPs lead to synonymous mutations and one SNP lead to nonsynonymous mutation. Synonymous mutations (71 %) were more common than nonsynonymous mutations (29 %) for both the C4H and CAD genes. Association genetics studies also revealed that four and six SNPs from the C4H and CAD genes respectively were significantly associated with the basic wood density of Kelampayan (p<0.05). Genetic variations identified by the SNP markers, once validated, will facilitate the selection of Kelampayan parental lines or seedlings with optimal quality through the gene-assisted selection (GAS) approach.